2010
DOI: 10.1111/j.1475-6773.2010.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mass Media Coverage on Timing and Annual Receipt of Influenza Vaccination among Medicare Elderly

Abstract: Objective To measure the association between mass media coverage on flu-related topics and influenza vaccination, regarding timing and annual vaccination rates, among the nationally representative community-dwelling elderly. Data Source 1999, 2000 and 2001 Medicare Current Beneficiary Survey (MCBS). Study Design Cross-sectional survival analyses during each of three influenza vaccination seasons between September 1999 and December 2001. The outcome variable was daily vaccine receipt. We measured daily medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 20 publications
1
59
1
1
Order By: Relevance
“…There is a need to consider how to avoid a similar media-evoked panic reaction in the future which causes damage to the public's health as the timing and type of broadcast can make a significant difference on the epidemic spread as change in attitudes and (lack of) knowledge can generally affect the long-term success of any information campaigns in influencing the course of an epidemic. It has been reported that timing and annual receipt of influenza vaccination appear to be influenced by media coverage, particularly by headlines and specific reports on shortage/delay [34]. Sun et al [27] consider a two-patch SIS model whereas we consider a single SEIHR.…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to consider how to avoid a similar media-evoked panic reaction in the future which causes damage to the public's health as the timing and type of broadcast can make a significant difference on the epidemic spread as change in attitudes and (lack of) knowledge can generally affect the long-term success of any information campaigns in influencing the course of an epidemic. It has been reported that timing and annual receipt of influenza vaccination appear to be influenced by media coverage, particularly by headlines and specific reports on shortage/delay [34]. Sun et al [27] consider a two-patch SIS model whereas we consider a single SEIHR.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of media coverage on vaccination uptake has been studied with respect to the influenza vaccine [6], HPV vaccine [7], and MMR vaccine [8,9]. Smith et al [8] focused on selective MMR nonrecipients, meaning children who received all recommended vaccinations except the MMR vaccine, and concentrated on media related to Wakefield et al's 1998 paper [10] and its now discredited link between the MMR vaccine and autism.…”
Section: Related Workmentioning
confidence: 99%
“…Because these data did not distinguish the EH and SH groups in the Hispanic population, the vaccination coverage rate among the EH and SH groups was obtained from our previous [19].…”
Section: Effectiveness Parametersmentioning
confidence: 99%
“…Our previous study found a strong association between nationwide TV network coverage on influenza-related topics and influenza vaccination among the Medicare elderly by analyzing the 1999 to 2001 Medicare Current Beneficiary Survey (MCBS) data [19]. In addition, the TV campaign was reported to be generally effective in changing health behavior (e.g., nutrition, physical activity, and use of tobacco, alcohol, and illicit drugs) and health service utilization (e.g., cancer screening, prevention of heart disease, immunization programs [for measles, mumps, and rubella], and antibiotic use) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%